2021
DOI: 10.1136/bmjopen-2020-041139
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of a two-stage attention-aware convolutional neural network for the automated diagnosis of otitis media from tympanic membrane images: a prediction model development and validation study

Abstract: ObjectivesThis study investigated the usefulness and performance of a two-stage attention-aware convolutional neural network (CNN) for the automated diagnosis of otitis media from tympanic membrane (TM) images.DesignA classification model development and validation study in ears with otitis media based on otoscopic TM images. Two commonly used CNNs were trained and evaluated on the dataset. On the basis of a Class Activation Map (CAM), a two-stage classification pipeline was developed to improve accuracy and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…This is often affected by using different otoscopy systems, such as a standard otoscope 26,27,29 and endo-otoscope. [3][4][5] A further challenge is that the diagnostic accuracy of the ML approaches is affected by the degree and type of pathological changes in the middle ear. For example, Cai et al 3 indicated that it is more difficult to distinguish between normal and OME, whereas there was difficulty in classifying the cases of cerumen and tympanostomy tube in the study by Livingstone et al 24 Therefore, to minimize this challenge, multi-label classifiers trained Not having access to big data is a common challenge when analyzing medical images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is often affected by using different otoscopy systems, such as a standard otoscope 26,27,29 and endo-otoscope. [3][4][5] A further challenge is that the diagnostic accuracy of the ML approaches is affected by the degree and type of pathological changes in the middle ear. For example, Cai et al 3 indicated that it is more difficult to distinguish between normal and OME, whereas there was difficulty in classifying the cases of cerumen and tympanostomy tube in the study by Livingstone et al 24 Therefore, to minimize this challenge, multi-label classifiers trained Not having access to big data is a common challenge when analyzing medical images.…”
Section: Discussionmentioning
confidence: 99%
“…2 MED has a number of forms, for example, tympanic membrane (TM) perforation, acute otitis media (AOM), otitis media with effusion (OME), and chronic otitis media (COM). 3 Without timely diagnosis and treatment, severe and persistent MED can lead to permanent hearing loss, developmental delay in children, and even lifethreatening complications. 4 Otoscopy or otoendoscopy is a clinical examination routinely used by healthcare pro.fessionals, including otologists, audiologists, pediatricians, family practitioners, and those who work in urgent and emergency care services.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies [25][26][27][28][29] compared the performance of image classification algorithms to human assessors. Of these, three studies compared the performance of the AI algorithm to human assessors using the same test set.…”
Section: Aiversushumanclassificationmentioning
confidence: 99%
“…The binary classification method of still color images of the eardrum has been used to identify the normal ear and otitis media, with accuracy rates of 73.1 and 68.3%, respectively (Tran et al, 2018;Cai et al, 2021). In both cases, color information was used to train the learning models.…”
Section: Discussionmentioning
confidence: 99%